(untitled) (Asamblea. Revista parlamentaria de la Asamblea de Madrid, 2024)
The purpose of monitoring the parliamentary activity carried out in the Madrid Assembly, the subject of this parliamentary chronicle, is to offer information related to the first session of the XIII Legislature, which runs from June 13 to December 31, 2023.